Analyzing the Good Governance of Public Sector Organizations Through Good Corporate Governance: A Case Study of PT. South Sulawesi Citra Indonesia South Sulawesi - Muh Alwi; Armin Arsyad; Badu Ahmad; Muhammad Yunus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
Effective corporate governance is unequivocally a framework that oversees and regulates companies, ensuring they generate value for all stakeholders. PERSERODA, formerly a local company, has undergone a transformation in line with legal provisions. This study aims to scrutinize the application of good corporate governance in the management of regional companies, specifically focusing on PERSERODA. Utilizing qualitative research methods, the research is conducted at PT. South Sulawesi Citra Indonesia, operating as PERSERODA in the South Sulawesi province. Primary data is gathered through in-depth interviews and participant observation. The findings reveal that the fundamental principles of good corporate governance have not been consistently and comprehensively applied in the company's operations, resulting in PERSERODA falling short of its potential contribution to the region. Implementing these principles thoroughly within a company can enhance both its performance and the quality of its output.